Evaluation Of Surgical Outcome Of Dual Mobility Total Hip Replacement (Indian Journal of Applied-Basic Medical Sciences, 2022)
INTRODUCTION;To reduce the incidence of instability and  dislocation rate following primary Total Hip Replacement (THR)  surgery, Dual Mobility Total Hip Replacement (DMTHR)  component has been developed. AIMS AND OBJECTIVES ;This study is aimed to assess the  functional result and complications following DMTHR. MATERIALS AND METHODS 26 patients who have undergone  DMTHR between June 2018 to February 2020 were included in  this retrospective study. Modified Harris Hip Score was used to  evaluate surgical and functional outcome. RESULT ;Out of 26 patients in this study, 17 were males and 9  were females. The mean age was 52 years (Range 21 to 81  years). As per Modified Harris Hip Score functional outcome was Excellent in 20 (77%), Good in 4 (15%), Fair in 1 (4%) and poor  in 1 (4%), patients. CONCLUSION Dual mobility total hip replacement provides  good hip range of movement and stability and is also associated with lower dislocation rate.
Keywords: Dual Mobility Total Hip Replacement; Dislocation; Modified Harris Hip Score